The Effect of Green Bean Extract To Increase of Pregnant Women's Upper Arm Circumference in The Primary Health Care Center of Gubug I Grobogan Regency - Siti Nur Khasanah; Dhita Aulia Octaviani; Intan Nugraheni (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2020)
Chronic energy deficiency (KEK) is a nutritional problem caused by lack of food intake in a long time. Based on the Basic Health Research (Riskesdas) in 2018 in Indonesia containing pregnant women with Chronic Energy Deficiency reaching 17.3%. This shows that there are still quite a lot of pregnant women who are malnourished in Indonesia. One of local foodstuffs that can be an alternative to meet the nutrition of pregnant women with mung beans. Mung beans are rich in macro, micro nutrients, vitamins B1, B2, amino acids, folic acid, protein, carbohydrates, Ca and phosphorus. This study discusses how to increase mungbean extract to increase upper arm circumference in pregnant women Energy Deficiency in the working area of the Public Health Center Gubug 1. This study was a study of one group with pre and post tests. The population of this study is pregnant women with Chronic Energy Deficiency according to inclusion criteria. The sampling technique is to use a purposive sampling technique. Giving mung bean extract is done for 30 days. The study showed the results of the measurement of the circumference of the upper arm before training (pre test) with after administration (post test) after being involved using paired t-test obtained p value (0.001) α (0.05). Means there is a significant difference between the circumference of the upper arm before the treatment round. From the research that is expected from health workers need to educate pregnant women for nutritious food, so pregnant women do not need Chronic Energy Deficiency. Nutritious food sources can be obtained from the environment around pregnant women and are easily available at affordable prices. Keywords: Mung bean extract; Chronic Energy Deficiency; Upper Arm Circumference